Hypoglycemic and Hypolipidemic Activities of Aloe vera Leaf Mucilage in Alloxan-Induced Diabetic Rats - Mediha Sefi; Mariem Chaâbane; Moez Refrafi; Najiba Zeghal (Mazandaran University of Medical Sciences, 2019)
The present study aimed to evaluate the hypoglycemic and hypolipidemic activities of Aloe vera mucilage in alloxan-induced diabetic rats. Adult male Wistar rats were assigned into 4 groups (6 rats/group), as follows: the first group (C) served as the controls. The second group of rats (AL) received a single subcutaneous dose of alloxan at 120 mg kg-1bw. These groups received 1 mL of NaCl 9%. The third group (AL+Av) represented diabetic rats treated with 1 mL of mucilage extracted from Aloe vera leaves. The fourth group (C+Av) corresponded to control rats administered with 1 mL of Aloe vera mucilage. NaCl or Aloe vera mucilage were intraparenterally injected to the rats. Diabetic rats exhibited significant hyperglycemia accompanied by glycosuria. We also observed a significant reduction in the liver weight and glycogen content of the specimen. A reduced level of serum insulin was also observed among diabetic rats. However, the levels of serum triglycerides and total cholesterol increased in alloxan-induced diabetic rats. Aloe vera mucilage administration to diabetic rats partially and totally corrected glycaemia and liver glycogen content and serum insulin level, respectively. The rats' lipid status has also been improved. Medicinal plants, including Aloe vera, are expected to correct hyperglycemia and hyperlipidemia in diabetic patients to prevent the adverse effects of synthetic drugs.